Management development programs and the aspired management style: a study in Malaysia - Juhdi, Nurita; Wan Jusoh, Wan Jamaliah; Supar, Norizah; Juhdi, Noor Hasni (Technical University of Kosice, 2015)
Purpose: The study was to examine the relationship between management development programs and the management styles used by junior executives and young managers. Design/methodology/approach: Data was collected using survey forms and all the respondents were below 45 years old. They were either professionals or holding middle to higher level positions. Findings: Only mentoring had significant relationships with all the seven management styles. Mentoring was also found as the only program which was significant predictor to all the management styles. Assessment programs were found having significant relationship with participative style with negative relationship. On-the-job development programs were only significantly related to two management styles. Delegating style was significantly related to all the management development programs. Ethical management style was only significant to mentoring. Research implications: HR practitioners should emphasize the use of mentoring with systematic mentoring programs. Research limitations: The correlation values among variables were weak-tomoderate and some variables suffered from low Cronbach’s alpha values.